1985
DOI: 10.1203/00006450-198504000-01079
|View full text |Cite
|
Sign up to set email alerts
|

1049 An outbreak of cryptosporidiosis in a day care center

Abstract: Proloneed unex~lained fever is a continuine ~roblem in a s s o c i a t e d w i t h s i g n i f i c a n t m o r b i d i t y and m o r t a l i t y f o r very low b i r t h w e i g h t (LBW) i n f a n t s , <1300gm, and i n f a n t-t o-i n f a n t t r a n s m i s s i o n h a s a p p a r e n t l y occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
6

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 0 publications
1
42
0
6
Order By: Relevance
“…The TRAP-C2 gene sequence analysis of oocyst specimens from several North American outbreaks, including an isolate from the Cranbrook outbreak, demonstrated that these two major genotypes could be associated with two different cycles of transmission, i.e., either zoonotic transmission, which has been mainly bovine-to-human, 4,5 or person-to-person transmission. 9,10 The analysis of patient isolates from the Cranbrook and Maine outbreaks using more than one polymorphic gene locus confirmed that the parasite genotype was an animal genotype. This showed that transmission was associated with exposure of these patients to cryptosporidiosis-infected animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TRAP-C2 gene sequence analysis of oocyst specimens from several North American outbreaks, including an isolate from the Cranbrook outbreak, demonstrated that these two major genotypes could be associated with two different cycles of transmission, i.e., either zoonotic transmission, which has been mainly bovine-to-human, 4,5 or person-to-person transmission. 9,10 The analysis of patient isolates from the Cranbrook and Maine outbreaks using more than one polymorphic gene locus confirmed that the parasite genotype was an animal genotype. This showed that transmission was associated with exposure of these patients to cryptosporidiosis-infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas, the transmission of cryptosporidiosis from person to person has been documented. [9][10][11] Molecular epidemiology has been used recently to characterize the genotype of C. parvum isolates from 5 North American cryptosporidiosis outbreaks and to associate parasite genotype with disease transmission cycles. 12 Several polymorphic gene loci such as the thrombospondin-related adhesion protein (TRAP-C2) gene, 12 the internal transcribed spacer 1 (ITS1), 13 the 18S rRNA gene, 14 the 190-kD oocyst wall protein gene, 15 the dihydrofolate reductase-thymidylate synthase gene, 16 an anonymous non-telomeric repetitive gene, 17 and a threonine-rich open reading frame (ORF) 18 have been amplified by the polymerase chain reaction (PCR) and identified by sequencing as well as restriction mapping.…”
mentioning
confidence: 99%
“…O criptosporídio tem sido relatado em todas as partes do mundo com uma prevalência, entre as crianças diarréi-cas, de 1,9 a 19% dos casos 1,5,6,9,14,18 e, no Brasil, entre 0,5 a 21,3% 2,10,12,16,20 . Os percentuais mais elevados têm sido observados entre crianças procedentes de famílias de baixas condições sócio-econômicas, nas quais a contaminação ambiental é elevada.…”
Section: Introductionunclassified
“…Cerca de 10% dos episódios diarréi-cos agudos na infância estão relacionados com os protozoários e, dentre estes, o Cryptosporidium sp, ocupa lugar de destaque 7,11,12,18 . Descrito inicialmente como agente etiológico importante entre indivíduos imunodeprimidos, posteriormente se constatou que se relacionava com quadros diarréicos agudos em pacientes imunocompetentes de todas as idades, de modo particular na criança 4,8,9,14,18,19,21 .O criptosporídio tem sido relatado em todas as partes do mundo com uma prevalência, entre as crianças diarréi-cas, de 1,9 a 19% dos casos 1,5,6,9,14,18 e, no Brasil, entre 0,5 a 21,3% 2,10,12,16,20 . Os percentuais mais elevados têm sido observados entre crianças procedentes de famílias de baixas condições sócio-econômicas, nas quais a contaminação ambiental é elevada.…”
unclassified
See 1 more Smart Citation